PENGARUH PENGGUNAAN MODEL AKTIVE LEARNING DENGAN STRATEGI CLARIFICATION PAUSES TERHADAP HASIL BELAJAR SEJARAH SISWA KELAS X SMA N 1 TEUNOM SEMESTER GANJIL TAHUN AJARAN, 2017-2018 - Sri Wahyuna; T Abdullah; Nurasiah . (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
Research entitled "The Influence of Group Investigation type Cooperative Learning model with reading quiz strategy on History Learning Achievement of Grade XI Students of Banda Aceh State High School 5" aims to: (1) analyze the influence of the model cooperative learning type group investigation with a reading quiz strategy on the historical learning achievement of class XI students of SMA Negeri 5 Banda Aceh; and (2) to explain factors that influence student achievement by using cooperative learning model type group investigation with a reading quiz strategy. The approach used is quantitative and qualitative approaches while the type of research is experimental. The population of this study were all students of class XI IPS in SMA Negeri 5 Banda Aceh which amounted to 110 students and consisted of 4 classes, and the sample was class XI IPS1 and XI IPS3 each class consisted of 24 students. Data collection techniques in this study use tests, documentation, and interviews. The results obtained are the use of the investigation group type learning model with a reading quiz strategy affecting the historical learning achievement of class XI IPS students of SMA Negeri 5 Banda Aceh. Based on the results of data processing using t-test analysis obtained the value at the level of 5% (α = 0.05) obtained t count = 3.06 at significant levels (α = 0.05) and odds (1-α), t (0, 95) (27) = 2.02 with dk = 24 - 1 = 23. Because 3.06 2.02, H1 is accepted. Factors that influence student learning presentation using cooperative learning model type group investigation with reading quiz strategy is that students are directly involved in finding the problem of the lesson that the teacher conveyed, so as to generate a sense of pleasure, interest and high motivation to be the best of classmates, even students also acknowledge the use of group investigation learning model with a reading quiz strategy by history teachers can facilitate students to understand the subject matter delivered by the teacher. Keywords: Group Investigation, Reading Quiz, Achievement